2020
DOI: 10.3390/met10050676
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Microwave and Induction Heating Applicator for Metal Making: Design and Testing

Abstract: The use of microwave heating in primary metallurgy is gaining an increasing interest due to the possibility to selectively process ores and to volumetrically heat large amounts of low-thermal conductivity minerals. In this paper the study, development and testing of a new applicator combining the use of microwave and induction heating for rapid reduction of metal containing oxides is described. Numerical simulation was used in order to achieve the proper control over heat generation, considering the use of mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The use of microwaves exhibits unique advantages such as rapid, volumetric, and selective heating, which can reduce process times and energy consumption [77], [78]. This is due to the different heating mechanism in microwave processing compared to conventional processing.…”
Section: Alternative Induration Methodsmentioning
confidence: 99%
“…The use of microwaves exhibits unique advantages such as rapid, volumetric, and selective heating, which can reduce process times and energy consumption [77], [78]. This is due to the different heating mechanism in microwave processing compared to conventional processing.…”
Section: Alternative Induration Methodsmentioning
confidence: 99%
“…This preliminary assessment confirmed that the dual-row injection TGR system could improve the furnace performance, especially in terms of gas utilization degree and total energy demand. Recently, the state-of-the-art technology of microwave heating that has attracted widespread attention in the field of pyro-metallurgy [12,13] has appeared as an option of supplying thermal energy to the H 2 -SF. However, there is so far very little information on the use of microwave heating in shaft furnaces.…”
Section: Introductionmentioning
confidence: 99%